ปริมาณคาร์บอนสะสมในต้นไม้ บริเวณมหาวิทยาลัยราชภัฏนครศรีธรรมราช CARBON STOCK OF TREES IN NAKHON SI THAMMARAT RAJABHAT UNIVERSITY - มากพันธ์, วัฒนณรงค์; รับไทรทอง, จิตติมา; แซะอาหลี, สุภาวดี (Srinakharinwirot University Journal of Sciences and Technology, 2019)
This study aims to assess the carbon stock of trees in Nakhon Si ThammaratRajabhat University By setting up the 50x300 m., sampling for 4 plots, and then recording the DBH (Diameter at Breast Height). The biomass was estimated using by allometric equation and carbon stock was calculated by multiplying the biomass with a 0.5 of conversion factor. As the result, the total of 1,653 trees in the study area was the highest. The first research plots were 615 trees or 37.20% and second research plots is least were 337 trees, accounting for 20.38%. Total of the carbon stock were 567,919.20 kilograms or 567.92 tons, the most is first research plots were 240,489.03 kilograms, or 42.35% and least is second research plots were 45,708.33 kilograms, or 8.05 %.